A biphasic model of lifespan in nematode Caenorhabditis elegans worm - Suhayl Mulla; Adele R. Ludlam; Aiman Elragig; Cathy Slack; Zita Balklava; Michael Stich; Alex Cheong (Royal Society Open Science, 2023)
Ageing research focuses on identifying lifespan modifiers and understanding and appropriately interpreting their effects. One of the most relevant quantities being studied is the shape of the survival curve that can reveal crucial information on the mechanism of action. Here, we introduce a bilogistic model to describe the shape of the lifespan curves of Caenorhabditis elegans populations. Using the corrected Akaike information criterion and the RMSE as goodness-of-fit tests, we show that the bilogistic model provides a better fit to the experimental data from nematode worms than other mathematical models and can identify and confirm biphasic lifespan data. Our parametric model offers a method to interpret replicate experiments data in terms of the shape parameters of the lifespan curve and enables robust statistical analysis of intra- and inter-group variance. We apply the model to novel lifespan data from C. elegans and Drosophila melanogaster and provide a rational statistical analysis of lifespan modifiers such as temperature and daf-16/FOXO mutation.